A Novel Homozygous Mutation of the AIRE Gene in an APECED Patient From Pakistan: Case Report and Review of the Literature - Pellegrino, Marsha; Bellacchio, Emanuele; Dhamo, Rudina; Frasca, Federica; Betterle, Corrado; Fierabracci, Alessandra (Frontiers in Immunology, 2018)
Autoimmune-Poly-Endocrinopathy-Candidiasis–Ectodermal-Dystrophy syndrome (APECED) is a rare monogenic recessive disorder caused by mutations in the autoimmune regulator (AIRE) gene. Criteria for the diagnosis of APECED is the presence of two of the following disorders: chronic mucocutaneous candidiasis, chronic hypoparathyroidism and Addison’s disease. APECED develops at high incidence in Finns, Sardinians and Iranian Jews and presents with a wide range of clinical phenotypes and genotypes. In this manuscript, we report the clinical, endocrinological and molecular features of a 16 years-old female patient from Pakistan living in Italy and presenting the major APECED clinical manifestations chronic mucocutaneous candidiasis, chronic hypoparathyroidism and primary adrenal insufficiency. Premature ovarian failure, chronic broncopneumopathy, vitiligo, Hashimoto’s thyroiditis emerged as associated diseases. In our patient, AIRE gene screening revealed the novel c.396G>C (p.Arg132Ser; p.R132S) mutation in homozygosity thus confirming APECED diagnosis. This is the first reported mutation within the nuclear localization signal that is associated with APECED. The NLS mutation affects the nuclear import of classical transcription factors through nuclear pore by recognition of nuclear import receptors, the importin α molecules. By displaying crystal structures of the peptide containing the KRK basic residue cluster bound to α importins, we show that p.R132S replacement in 131-KRK-133 does not reproduce these interactions. Thus, we propose that the novel mutation exerts its pathogenetic effect by impairing the nuclear import of the Aire protein. The present case report is added to a limited series of Pakistani APECED patients that we reviewed from the scientific literature, mostly diagnosed on clinical findings.